Antiretroviral Regimen Durability and Success in Treatment-Naive and Treatment-Experienced Patients by Year of Treatment Initiation, United States, 1996–2011. (1st January 2016) - Sheth, Anandi N.; Ofotokun, Ighovwerha; Buchacz, Kate; Armon, Carl; Chmiel, Joan S.; Hart, Rachel L.D.; Baker, Rose; Brooks, John T.; Palella, Frank J.
Abstract : Background: Although modern combination antiretroviral therapy (cART) regimens are better tolerated and less complex than earlier treatments, regimen modification or discontinuation remains a concern. Methods: We studied HIV Outpatient Study (HOPS) participants who initiated the first or second cART regimens during: 1996–1999, 2000–2003, 2004–2007, and 2008–2011. We analyzed regimen durability (time to regimen modification) and success (achieving undetectable plasma HIV RNA) for the first and second cART regimens using Kaplan–Meier curves and log-rank tests, and examined factors associated with durability and success of the first cART regimen using proportional hazards models. Results: Durability of cART was progressively longer for cART regimens initiated in more recent periods: median first cART regimen durations were 1.0, 1.1, 2.1, and 4.6 years in 1996–1999, 2000–2003, 2004–2007, and 2008–2011, and the median second cART durations were 0.9, 1.2, 2.8, and 3.9 years, respectively (both P < 0.001). Comparing 1996–1999 and 2008–2011, the percentage of patients who achieved an undetectable HIV RNA within 6 months of first cART initiation increased from 65% to 81% and from 63% to 80% on second cART (both P < 0.001). Among patients initiating first cART during 2008–2011, black non-Hispanic/Latino race/ethnicity and ≥twice-daily dosing were significantly associated with higher rates of regimen modification ( P < 0.05), and higher baseline HIV RNA levels were associated with failure to achieve an undetectable HIV RNA ( P < 0.001). Conclusions: Among HIV-infected U.S. adults in routine HIV care, durability of the first and second cART regimens and the likelihood of prompt virological suppression increased during 1996–2011, coincident with the availability of more tolerable, less complex cART options.